International Science and Practice Conference "Historical and Cultural Heritage of the People of Central Asia: prospects of development and problems of preservation (September 14–15, 2012, Kyzyl) - ., . . (The New Research of Tuva, 2012)
International Science and Practice Conference "Historical and Cultural Heritage of the People of Central Asia: prospects of development and problems of preservation (September 14–15, 2012, Kyzyl)